Sosialisasi Peracangan Bangunan Area Peternakan Al-Amin Science dan Industrial Park (Living Lab) Berbasis GAHP di Desa Sampecita Kecamatan Kutalimbaru Kabupaten Deli Serdang - Faurantia Forlana Sigit; Purwo Siswoyo; M. Aly Mujahidin; Dara Wisdianti (Arsil Media, 2023)
The Al Amin Science and Industrial Park (Living Lab) is a projected area intended to become a center for field laboratories and workshops accommodating all study programs at UNPAB. The area is also planned to become Ecoedutourism (Eco-educational tourism). One of the functions to be developed in this area is livestock farming. In the face of the ASEAN Economic Community (AEC) in 2015, especially in the food sector, specific standardization is required for livestock products. Therefore, the concept of Good Animal Husbandry Practices (GAHP) needs to be implemented. Thus, there is a need for planning the design concept of supporting buildings in the livestock area of the Al Amin Science and Industrial Park (Living Lab) that considers GAHP. The implementation of GAHP aims to ensure that the livestock products produced are safe for consumption with appropriate quality for consumers. Additionally, it ensures that livestock products are produced correctly without causing environmental, health, safety, and welfare losses/damages to workers in the livestock sector. The objective of this research is to produce a design for supporting buildings in the livestock area of the Al Amin Science and Industrial Park (Living Lab) based on GAHP. The results of this design are expected to guide the development of supporting buildings in the livestock area of the Al Amin Science and Industrial Park (Living Lab).